Glucose-6-phosphate dehydrogenase deficiency and chronic haemolysis in an English family - Huskisson, E. C. (1970)
Three male members of an English family with chronic haemolytic anaemia due to glucose-6-phosphate dehydrogenase deficiency are reported. The disease was symptomless in one adult, but crises, caused either by increased haemolysis or failure of marrow compensation, occurred in two children. They were typically precipitated by trivial infection. Two normal female members of the family were obligatory heterozygotes. A hitherto undescribed `slow' variant of the enzyme was identified electrophoretically.